PERSEPSI MASYARAKAT TENTANG PERAN PETANI PEREMPUAN DI DESA SIMPANG KUBU KECAMATAN KAMPAR KABUPATEN KAMPAR - Derry Pelangi; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research i s motivated by the role of women in rice farmingwhich is generally carried out by men but not in the intersection village where the task of taking care of rice farming in the Simpang Kubu village is the role and responsibility of women. The formulation of the problem of this research is "What is the communityperception about the role of women farmers in Simpang Kubu Village, Kampar District, Kampar Regency". the purpose of this study was to "To find out how people's perceptions about the role of women far mers in Simpang Kubu Village, Kampar Regency". Data collection techniques in this study were observation, interviews and questionnaires. Data analysis techniques in this study used descriptive qualitative methods. The results in this study are people's per ceptions about the role of women farmers both in their roles in the family and in agriculture are good or are considered normal and are common in the community.Key Words : Community Perception, Role and Women